IMPLEMENTASI KEBIJAKAN KETERTIBAN TERMINAL PENUMPANG - S, Arbi Winarko; Sahuri, Chalid (Jurnal Kebijakan Publik, 2013)
The purpose of this study was toanalyze the implementation of the policy in order Dumai City passenger terminal. Design used inthis study is a qualitative method. This method of choice for researchers is expected to be able touncover the reality on the field and more sensitive and adaptive to the role of various factors inthe study as well as more sensitive to information that is descriptive and try to maintain theintegrity of objects studied. The results indicate the implementation of policies penelitina orderpassenger terminal in accordance with the regulations of higher, namely Law No. 22 of 2009 onRoad Traffic and Transport as well as Minister of Transportation No. 31 of 1995 on Road TransportTerminal. However, enforcement action against passenger vehicles do find problems where thestructure of UPT. Passenger Terminal is currently not in accordance with the volume of work islarge enough.